Frequency of Toxocariasis among Patients Clinically Suspected to Have Visceral Toxocariasis: A Retrospective Descriptive Study in Sri Lanka - Devika Iddawela; Kiruthiha Ehambaram; Dhilma Atapattu; Kalyani Pethiyagoda; Lakmalee Bandara (Journal of Parasitology Research)
Introduction. Human toxocariasis is caused by several species of the nematode Toxocara. Two common clinical syndromes are ocular and visceral larva migrans. Objectives. To determine the Toxocara antibody positivity in clinically suspected VLM patients and to describe demographic factors and clinical manifestations of seropositive patients. Methods. 522 clinically suspected patients were studied between 1993 and 2014. Relevant data was gathered from referral letters. Serum samples were subjected to Toxocara antigen ELISA. Results. Overall, seropositivity was 50.2% (262), of which 109 (40.8%) were positive at high level of Toxocara antibody carriage and 153 (58.4%) were positive at low levels. The seropositives ranged from 3 months to 70 years (mean = 7.8). Younger age group had higher levels of seropositivity and it was statistically significant. Majority of children under 5 years were seropositive (47.7%, n=125). Seropositivity was common in males (55.3%, n=145). Clinical manifestations of seropositives include lymphadenopathy (24.1%) skin rash (22.5%), dyspnoea (21.7%), fever (21%), hepatosplenomegaly (9.2%), and abdominal pain (3.8%). 197 (75.2%) seropositive cases had eosinophilia. These symptoms were not statistically significant. Conclusions. This study confirms toxocariasis as an important cause of childhood ill health identifying common clinical symptoms recommending preventive measures to limit transmission.